174 MECHANICAL VENTILATION AFFECTS EPIGENETIC DETERMINANTS IN PRETERM LAMB LUNGS. (1st January 2005) - O'Brien, E.; Zhao, L.; McKnight, R.; Fu, Q.; Yu, X.; Albertine, K.; Lane, R.
Abstract : Background: Volume trauma contributes significantly to the pathogenesis of CLD characterized by alveolar simplification. Though the molecular mechanism that leads to this morbidity is unknown, the link between an early transient insult and a postnatal phenotype suggests an epigenetic phenomenon. Epigenetic phenomena induce persistent changes in gene expression by altering determinants of chromatin structure such as DNA methylation and histone modifications. Objective: We hypothesized that volume trauma alters determinants of chromatin structure in preterm lamb lungs in association with phenotypic changes consistent with alveolar simplification. Design/Methods: Our lab uses a well established preterm lamb model of CLD where 3 days of conventional mechanical ventilation (CMV) results in decreased secondary crest formation consistent with alveolar simplification. To test our hypothesis we proposed to determine if volume trauma: (1) alters global and promoter specific DNA methylation; (2) alters DNA methyltransferase 1 (DNMT1), an enzyme involved in DNA methylation, mRNA or protein; and (3) is associated with modifications of specific histone H3 sites. All experiments were performed in preterm lambs managed with 3 days of nCPAP, our gold standard for preterm alveolar formation. Results: We found that CMV induced volume trauma increases global and promoter specific DNA methylation in preterm lamb lungs (CMV 118 ± 5.3% of nCPAP treated group, p≤0.01, n=4, ± SEM). Interestingly, DNMT1 protein is significantly increased (CMV DNMT1 protein 153 ± 11 % of control, p≤0.05, n=4, ± SEM). As one would expect based upon DNA hypermethylation, volume trauma significantly decreased acetylation of lysine (K) 9 and 14 on histone 3 (CMV H3/K9 77.5 ± 6.8 % and H3/K14 53.2 ± 23% of nCPAP treated controls n=4, p≤0.05, ± SEM), whereas methylation of H3/K9 was not significantly altered. Conclusion: Volume trauma is associated with modifications in epigenetic determinants in preterm lambs. These findings are intriguing for they demonstrate an association between volume induced lung injury and alterations in chromatin structure. We speculate that volume trauma affects chromatin structure yielding different patterns of gene expression thereby changing the phenotype of the preterm lamb lung. (Sponsored by the Univ. of Utah Department of Pediatrics CHRC and the CHRCDA).